Longitudinal evaluation of endothelial markers in children and adolescents with familial hypercholesterolemia.: FMD in paediatric heFH - Bruzzi, Patrizia; Predieri, Barbara; Madeo, Simona; Lami, Francesca; Iughetti, Lorenzo (Acta Biomedica Atenei Parmensis, 2021)
Background and aim: Children with heterozygous familial hypercholesterolemia (heFH) are at risk of premature atherosclerosis. Aims of this study were: (a) to longitudinally evaluate the endothelial dysfunction, estimated through brachial flow mediated dilation (FMD), as first sign of subclinical atherogenesis in a group of children and adolescents affected by heFH in comparison to normo-lipidemic controls, and (b) to identify predictive factors influencing the endothelial function and its development in the same cohort of patients.Methods: This is a prospective, longitudinal and cross-sectional study. Physical examination, plasma lipid profile and brachial artery FMD were measured at baseline and after follow-up.Results: At baseline, FMD did not differ between heFH children (n.24, median age 9.71) and controls (n. 24, median age 10.29) (7.67 ± 9.26 vs. 11.18 ± 7.28 %, p 0.09). Nevertheless, during follow-up (median length of lipid-lowering diet 4.52 years), FMD got worse in 54% of heFH subjects and its worsening correlated to the increasing of low-density lipoprotein cholesterol (r -0.21, p < 0.05). Moreover, being male (β -0.46, p 0.03), undergoing puberty (β -0.61, p 0.03) and increasing of body mass index standard deviation score (β -0.39, p 0.03) were identified as main independent predictor factors of FMD drop.Conclusions: During the first decades of life, not only hypercholesterolemia, but also clusters of pro-atherogenic conditions and their persistence, could affect the endothelial function and its trend. (www.actabiomedica.it)